Domains required for nucleic acid binding activities in chloroplast ribonucleoproteins. - Ye, L (1992)
Five ribonucleoproteins (or RNA-binding proteins) from tobacco chloroplasts have been identified to date; each of these contains an acidic N-terminal domain (24-64 amino acids) and two conserved RNA-binding domains (82-83 amino acids). All five ribonucleoproteins can bind to ssDNA and dsDNA but show high specificity for poly(G) and poly(U). Here we present the nucleic acid binding activity of each domain using a series of deletion mutant proteins made in vitro from the chloroplast 29 kDa ribonucleoproteins. The acidic domain does not have a positive effect on binding activities and proteins lacking this domain show higher affinities for nucleic acids than the wild-type proteins. Mutant proteins containing single RNA-binding domains can bind to poly(G) and poly(U), though with lower affinities than proteins containing two RNA-binding domains. The spacer region (11-37 amino acids) between the two RNA-binding domains does not interact with poly(G) or poly(U) by itself, but is required for the additive activity of the two RNA-binding domains. Proteins consisting of two RNA-binding domains but lacking the spacer have the same activity as those containing only one RNA-binding domain. Possible roles for each domain in chloroplast ribonucleoproteins are discussed.